2010
DOI: 10.1097/mcg.0b013e3181b5c789
|View full text |Cite
|
Sign up to set email alerts
|

Differential Diagnosis for Intrahepatic Biliary Cystadenoma and Hepatic Simple Cyst

Abstract: Cystic fluid carbohydrate antigen 19-9 levels and carcinoembryonic antigen levels were not useful for differential diagnosis of BCA vs. HSC. BCA were more common than HSCs in females, patients with a septum, and patients with septal thickening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(38 citation statements)
references
References 10 publications
3
35
0
Order By: Relevance
“…On ultrasound, cystic nature of the lesion with multiple loculi, septations, and internal echoes, with papillary projections [9, 15], is typical. The cyst is well-demarcated and thick-walled, globular or ovoid with a noncalcified wall [79, 27]. Doppler study may show the vascular flow within the lesion [28].…”
Section: Discussionmentioning
confidence: 99%
“…On ultrasound, cystic nature of the lesion with multiple loculi, septations, and internal echoes, with papillary projections [9, 15], is typical. The cyst is well-demarcated and thick-walled, globular or ovoid with a noncalcified wall [79, 27]. Doppler study may show the vascular flow within the lesion [28].…”
Section: Discussionmentioning
confidence: 99%
“…(56) Simple hepatic cysts have a better-defined tissue/fluid interface on imaging than BCT (Figure 3) . (57) In addition, Choi and colleagues (58) identified the presence of a septum and septal thickening as significant predictors of BCA versus simple hepatic cysts in their series of 31 patients. Echinococcal cyst and liver abscesses are the two other cystic liver lesions that sometimes can be difficult to differentiate from BCTs.…”
Section: Imagingmentioning
confidence: 99%
“…The role of cyst fluid CEA, CA19-9, and serum tumor markers remains controversial. (45, 56, 58, 70) Although many providers may obtain a CA19-9, the sensitivity and specificity are not high enough to differentiate a BCA from a BCAC. Moreover, fine needle aspiration (FNA) of suspected BCAC has been associated with pleural and peritoneal dissemination.…”
Section: Imagingmentioning
confidence: 99%
“…[9] CA19-9 may not contribute to the differential diagnosis of congenital hepatic cysts with intracystic hemorrhage. [10] Choi et al [11] showed that CA19-9 and carcinoembryonic antigen levels in the cystic fluid were of little significance for differentiating between biliary cystadenoma and a simple hepatic cyst. Bertino et al [12,13] showed that serum CA19-9 levels were frequently elevated in chronic viral hepatitis and hepatic cirrhosis.…”
Section: Discussionmentioning
confidence: 99%